Neurological implications of COVID-19: a review of the science and clinical guidance. Issue 2 (14th December 2020) - Tan, Lynn; Lin, Zhiliang Caleb; Ray, Jason; Wesselingh, Robb; Oxley, Thomas J; McFadyen, James; Kapoor, Mahima; Hutton, Elspeth
Abstract : COVID-19 is a significant global health burden. The pulmonary morbidity and mortality of COVID-19 is well described, however, there is mounting evidence of neurological manifestations of SARS-CoV-2, which may be of prognostic significance. This paper summarises the available evidence in order to provide clinicians with a concise summary of the peripheral and central neurological manifestations of COVID-19, discusses specific issues regarding the management of chronic neurological disease in the context of the pandemic, and provides a summary of the thrombotic implications of the disease for the neurologist.